2012
DOI: 10.5130/ajceb.v12i3.2537
|View full text |Cite
|
Sign up to set email alerts
|

Assessing occupant comfort in an iconic sustainable education building

Abstract: The building that houses the Mirvac School of Sustainable Development at Bond University is the first educational building to achieve a six Green Star rating from the Green Building Council of Australia. It has won numerous awards since opening in August 2008 including being judged the RICS (Royal Institution of Chartered Surveyors) Sustainable Building of 2009. After more than two years in use a post-occupancy evaluation study was carried out to assess the performance of the building from the viewpoint of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…It collated paper-based occupant questionnaire responses over a 20-year period [11,12]. Analysing 177 occupant satisfaction surveys stored in the BUS database, Leaman and Boardass observed that certain discomforts are common in many 'green intent' buildings [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It collated paper-based occupant questionnaire responses over a 20-year period [11,12]. Analysing 177 occupant satisfaction surveys stored in the BUS database, Leaman and Boardass observed that certain discomforts are common in many 'green intent' buildings [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They believe removing these discomforts will make occupants happier than providing additional features that they like. Using BUS methodology, Best and Purdey studied user satisfaction levels of a green university building in a warm temperate climate in Australia [11]. Their sample included both resident and transient users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…reveals that they tend to comprise of qualitative and/or quantitative methods (Table III), but with a diverse set of tools and methods that do not seem to be widely applicable, thereby forming a fragmented whole. Although a few BPE techniques such as the Building Use Studies (BUS) questionnaire are beginning to be used internationally (Brown et al , 2010; Best and Purdey, 2012; Deng et al , 2017) to evaluate user perception and satisfaction, there seems to be a general lack of a commonly agreed methodology for conducting evaluations, leading to inconsistencies in data collection, data analysis, reporting and communication of findings.…”
Section: Review Of Existing Bpe Studies In the Uk And Globallymentioning
confidence: 99%
“…Further evidence that Australian rating tools may simply be used for “greenwashing” – pretending to be environmentally friendly while actually only wishing to be seen as such – can be found in studies that compare the performance perceptions of the owners and managers of a green rated building with those of the employees and occupiers of the building (Best and Purdey, 2012).…”
Section: How Accurate Are Rating Tools At Assessment the Sustainability Of A Buildingmentioning
confidence: 99%